Effect of Renin-Angiotensin-Aldosterone System Blockade Therapy on Incidence of Contrast-induced Nephropathy in Patients with Chronic Kidney Disease - Spatz, Christin (2012)
INTRODUCTION: The incidence of contrast-induced nephropathy (CIN) ranges between 10% and 50% among high-risk patients. Whether medications that affect rennin-angiotensin-aldosterone system (RAAS) have any impact on the development of CIN remains uncertain. MATERIALS AND METHODS: We performed a retrospective study of patients with CKD stages 3 and 4 who were either on or off RAAS blockade therapy at the time of coronary angiography. Development of CIN was defined by a 25% increase of serum creatinine from baseline or an increase in serum creatinine by 0.5 mg/dL from baseline. Serum creatinine values were recorded before contrast exposure and for 5 days after coronary angiography. RESULTS: A total of 178 patients with CKD who had coronary angiography during the study period were included, of whom 62 (35%) were on ACE inhibitors, 12 (7%) were on ARBs, and 1 (1%) was on combination of ACE inhibitors and ARBs. The estimated glomerular filtration rate was 44.0 ± 11.5 mL/min. The odds ratio of acute kidney failure on day 5 was 0.73 (95% confidence interval, 0.31 to 1.69) for the ACE inhibitors and 0.46 (95% confidence interval, 0.06 to 3.70) for ARBs. Multivariable analysis revealed the findings to be independent of demographic variables, comorbidities, type of contrast medium, and the prophylactic strategies. CONCLUSIONS: Patients on RAAS blockade therapy before contrast exposure did not have an increased incidence of CIN. There was also no increased incidence of CIN with ACE inhibitors or ARBs in the subgroups at higher risk, such as those with diabetes mellitus.